Hubungan Kecerdasan Adversitas dan Self Efficacy Dengan Motivasi Belajar Pada Siswa SMA Negeri 6 Banda Aceh - Siti Syapiah Bintang; Wiwik Sulistyaningsih; Suryani Hardjo (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2019)
This research aims to examine the relationship between the intelligence of adversity and self efficacy with learning motivation. The research subjects were 70 students of SMA Negeri 6 Banda Aceh.Sampling technique  in this study by using purposive sampling technique. Measurers used  in this  study  are  the  scale  0f adversity quetion, the scale of self efficacy and  the  scale of   learning motivation. Data in multiple regression analysis showed that there was a very significant positive relationship between intelligence of adversity and self efficacy with learning motivation. This is shown by the coefficient of Freg = 62,364; Rx12y = 0.807 and p 0.001. The effective contribution percentage of both independent variables (adversity and self efficacy) to learning motivation was 65.1%. From these results we have known that there was still 34.9% contribution from other factors in motivation to learn.